Capturing the Severity and Impairment Associated With Depression: The Overall Depression Severity and Impairment Scale (ODSIS) Validation in a Spanish Clinical Sample - Mira, Adriana; González-Robles, Alberto; Molinari, Guadalupe; Miguel, Clara; Díaz-García, Amanda; Bretón-López, Juana; García-Palacios, Azucena; Quero, Soledad; Baños, Rosa; Botella, Cristina (Frontiers in Psychiatry, 2019)
Background: The Overall Depression Severity and Impairment Scale (ODSIS) is a self-report scale designed to evaluate the severity and functional impairment associated with depression. Objective: This study evaluated the psychometric properties of the online version of the ODSIS in Spanish outpatients with depression and anxiety disorders. Method: Patients with a main diagnosis of a depressive (n = 283) or anxiety disorder (n = 191) and a mean age of 38.15 (SD = 12.06) were evaluated with a clinical diagnostic interview and measures assessing depression, anxiety, positive and negative affect, and quality of life. Factorial structure, internal consistency, convergent and discriminant validity and cutoff scores were analyzed. Results: Consistent with previous validations of the instrument, Confirmatory Factor Analysis showed a unidimensional factor structure. Furthermore, the results obtained supported the internal consistency and construct validity of the ODSIS scores. A score of 5 was found to meet the criteria used in this study for the optimal cutoff score. Conclusion: The results obtained in this study show that the Spanish version of the ODSIS delivered online is an adequate tool to assess the depression-related severity and impairment in a brief and easy fashion.